(3LhGH eSCdI NHQ eGQjI GdbHWjIs - (3eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe GdYcHQqj, CHh YHO Gddg, GdeajO, hjYQa HGHf GdeYde , J (B413 (3g`s ((3eMeO Hf WGgQ GdSeGhi s)
(3ChdgG (B:s
(3SCdfi CWGd Gddg HbGA GdSjO GdaGVd QLd ef GdeYJRdI Yf GdNHQ GdeQhi Yf GdfHi Udi Gddg Ydjg hSde hBdg ai bUI eGQjI GdbHWjI QMegG Gddg s
(3BNQgG (B:s
(3hdG jfHZi ddYGbd Cf jXde faSg HecGHQI GdMb fLRJ HMeO Gddg hUdhGJg Ydi eMeO hBdg s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(998) s
Keywords: (3GdJhMjO hGdedd hGdfMds